Disparities in access to deep brain stimulation - Schmidt, Franziska; Martinez-Torres, Irene; Germann, Jürgen; Hajiabadi, Mohammad Mehdi; Bichsel, Oliver; Sarica, Can; Lozano, Andres M. (Stereotactic and functional neurosurgery, 2025)
Background: Deep brain stimulation (DBS) is a well-established treatment for several neurological and neuropsychiatric conditions, including movement disorders such as Parkinson’s disease, essential tremor, and dystonia, as well as Gilles de la Tourette’s syndrome, epilepsy, and obsessive-compulsive disorder. Summary: In recent years, research has expanded to explore the potential of DBS for other indications, including dementia, addiction, disorders of consciousness (e.g., minimally conscious state), and eating disorders. Over the past 3 decades, significant technological advancements have been made in DBS devices, including improvements in electrode design, stimulation parameters, and battery life. However, despite these technological innovations, equitable access to DBS has not progressed at a similar pace. Barriers to access remain a persistent challenge globally, influenced by socioeconomic, geographic, systemic, and policy-related factors. Key Message: This review summarizes the current literature on access to DBS, highlighting disparities, challenges, and potential strategies to improve availability and equity in its application.